Landscape evolution associated with the 2014–2015 Holuhraun eruption in Iceland - Bonnefoy, Léa; Hamilton, C.W.; Scheidt, S.P.; Duhamel, S.; Höskuldsson, A.; Jónsdottir, I.; Thordarson, T.; Münzer, U. (Journal of Volcanology and Geothermal Research, 2019)
International audience The 2014–2015 Holuhraun eruption in Iceland developed between the outlet glacier Dyngjujökull and the Askja central volcano and extruded a bulk lava volume of over 1 km3 onto the floodplain of the Jökulsá á Fjöllum river, making it the largest effusive eruption in Iceland during the past 230 years. Time-series monitoring using a combination of traditional aerial imaging, unmanned aerial systems, and field-based geodetic surveys, established an unprecedented record of the hydrological response of the river system to this lava flow. We observed: (1) the formation of lava-dammed lakes and channels produced during dam-breaching events; (2) percolation of glacial meltwater into the porous and permeable lava, forming an ephemeral hydrothermal system that included hot pools and hot springs that emerged from the lava flow front; and (3) the formation of new seepage channels caused by upwelling of water around the periphery of the lava flow. The observations show that lava flows, like the one produced by the 2014–2015 Holuhraun eruption, can cause significant hydrological changes that continue for several years after the lava is emplaced. Documenting these processes is therefore crucial for our interpretation of volcanic landscapes and processes of lava–water interaction on both Earth and Mars.